Anti-Collapsing Response-Mediating Protein-5 Antibody–Positive Paraneoplastic Perioptic Neuritis without Typical Neurological Symptoms. (2nd January 2017) - Igarashi, Nozomi; Sawamura, Hiromasa; Kaburaki, Toshikatsu; Aihara, Makoto
ABSTRACT: A 68-year-old male presented with blurred vision in both eyes. Ophthalmoscopy revealed bilateral prominent disc swelling and vitritis. No systematic neurological symptoms were observed. Magnetic resonance imaging revealed bilateral meningeal enhancement of the optic nerve. Small cell carcinoma was found, and antibodies against collapsing response-mediating protein-5 (CRMP-5) were detected in the serum. Ophthalmological manifestations disappeared during a decrease in tumour size with treatment for the malignancy. This case report describes this rare case of anti-CRMP-5 antibody–positive paraneoplastic perioptic neuritis without neurological symptoms, showing that prompt diagnosis and timely treatment of the underlying tumour are crucial to prevent increased levels of autoantibodies and irreversible damage to the nervous system.